Spread of Linezolid-Resistant Enterococcus spp. in Human Clinical Isolates in the Czech Republic - Lucia Mališová; Vladislav Jakubů; Katarína Pomorská; Martin Musílek; Helena Žemličková (MDPI AG, 2021)
The aim of this study was to map and investigate linezolid resistance mechanisms in linezolid-resistant enterococci in the Czech Republic from 2009 to 2019. Altogether, 1442 isolates of Enterococcus faecium and Enterococcus faecalis were examined in the National Reference Laboratory for Antibiotics. Among them, 8% of isolates (n = 115) were resistant to linezolid (E. faecium/n = 106, E. faecalis/n = 9). Only three strains of E. faecium were resistant to tigecycline, 72.6% of isolates were resistant to vancomycin. One isolate of E. faecium harbored the cfr gene. The majority (87%, n = 11) of E. faecium strains were resistant to linezolid because of the mutation G2576T in the domain V of the 23S rRNA. This mutation was detected also in two strains of E. faecalis. The presence of the optrA gene was the dominant mechanism of linezolid resistance in E. faecalis isolates. None of enterococci contained cfrB, poxtA genes, or any amino acid mutation in genes encoding ribosomal proteins. No mechanism of resistance was identified in 4 out of 106 E. faecium linezolid resistant isolates in this study. Seventeen sequence types (STs) including four novel STs were identified in this work. Clonal complex CC17 was found in all E. faecium isolates.